New record of the sponge-dwelling shrimp Typton distinctus Chace, 1972 (Decapoda: Caridea: Palaemonidae) in São Paulo State, Brazil - Moraes, Isabela R. R.; Bergamasco, Giovanna R.; Santos, Rafael C.; Antunes, Mariana; Soledade, Guidomar O.; Costa, Rogerio C.; Castilho, Antonio L. (Zootaxa, 2020)
Among the Caridea Infraorder, the palaemonid shrimp from the genus Typton Costa, 1844 are commonly found in association with sponges, frequently feeding on the tissues of their hosts ((Ďuriš et al. 2011; Almeida et al. 2014; Pachelle et al. 2015; Soledade et al. 2017). Typton is mostly characterized by morphological features related to their sponge-dwelling lifestyle, as a simple and compressed rostrum, carapace smooth and antennal spines present, antennae extremely reduced and scaphocerite rudimentary. Mandible without palp, incisor process normal, reduced or absent. Second legs unequal, asymmetrical, without molar process on major chela (Bruce, 1972)